Constructing Religion Without the Social: Durkheim, Latour, and Extended Cognition - Day, Matthew (2009)
Abstract. I take up the question of how models of extended cognition might redirect the academic study of religion. Entering into a conversation of sorts with Emile Durkheim and Bruno Latour regarding the “overtakenness” of social agency, I argue that a robust portrait of extended cognition must redirect our interest in explaining religion in two key ways. First, religious studies should take up the methodological principle of symmetry that informs contemporary histories of science and begin theorizing the efficacy of gods as social actors. Second, theorists of religion should begin noting how the work required to construct spaces in which the gods appear depends on the construction of disciplined and capable subjects.
Keywords: sociology of associations; Bruno Latour; extended cognition; Emile Durkheim